2013
DOI: 10.14710/jitaa.38.4.233-238
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Digestive Tract Development of Young Broiler Chickens Fed Mash Basal Diet Supplemented With Rice Hulls or Wheat Pollard at Different Levels

Abstract: ABSTRAKSebuah penelitian dilakukan untuk mengetahui pengaruh suplementasi sumber polisakarida nonpati (NSP) tidak-larut yang berbeda pada level 0, 20, 40, 60 g/kg terhadap performan dan perkembangan saluran pencernaan ayam broiler muda (doc-21 d). Hasil penelitian menunjukkan bahwa tidak ada interaksi antara sumber dan level NSP tidak-larut pada setiap variabel yang diukur. Efek signifikan hanya didapatkan pada level NSP tidak-larut. Ayam broiler muda yang diberi ransum bentuk mash yang disuplementasi dengan 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The result showed that the weight of the gizzard, small intestine, and pancreas was not affected by treatment diets. This result was similar to Hartini et al (2013), who reported that the GIT weight including gizzard, pancreas, and part of the small intestine was not affected by the addition of rice hull up to 6% in the diet based on corn and soybean. Sadeghi et al (2015) and Incharoen (2013) also reported no increase in gizzard weight by the inclusion of rice hulls at 3% and 10%, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The result showed that the weight of the gizzard, small intestine, and pancreas was not affected by treatment diets. This result was similar to Hartini et al (2013), who reported that the GIT weight including gizzard, pancreas, and part of the small intestine was not affected by the addition of rice hull up to 6% in the diet based on corn and soybean. Sadeghi et al (2015) and Incharoen (2013) also reported no increase in gizzard weight by the inclusion of rice hulls at 3% and 10%, respectively.…”
Section: Resultssupporting
confidence: 90%